NEWSPAPER REPRESENTATION OF PUBLIC PERSPECTIVES ON DEBT INCREASE BY NIGERIA’S STATE GOVERNMENTS - AFULIKE, Don Christian; EKE, Obinna Nathclinton; IHECHU, I Paschal; ANUMADU, V Adaeze (Socialscientia: Journal of Social Sciences and Humanities, 2018)
Nigeria became a credit worthy nation again after the Paris Club of creditors agreed to cancel its massive debt in 2006. The debt was incurred by successive governments via borrowing. Reports on debt sustainability by Debt Management Office (DMO), showed an increase in debts by Nigeria’s state governments, with accumulation of arrears and new issuance bonds challenge of revenue depletion, over concentration on oil and gas, infrastructural decay and mismanagement. This paper employed desk research method to look at the issues surrounding how newspapers in Nigeria reported public opinion on Nigeria’s debt increase. The review of a plethora of literature revealed that accumulation of domestic debt is now a common phenomenon of state governments’ development. The study recommended that the state governments should improve in the availability of social infrastructure as the chief executives and other leaders must be self-disciplined to cut their appetite for over borrowing, while making use of the media to address issues of social unrest and insecurity that is inimical to economic development; thus targeting infant industries, small scale businesses and the professionals.